The impact of management on the sustainability of the community development projects in Mutale Local Municipality, Limpopo Province - Ravhura, Thiathu Ishmael (My University, 2010)
This study focuses on the impact of management on the sustainability of the community development projects in Mutale Local Municipality. Mutale Local Municipality (MLM) is in the Limpopo Province and is about 262km north of Polokwane. MLM is predominately rural and it has two towns, which are: Mutale and Masisi. Fighting poverty is a serious challenge facing the people from this area today. It is interesting to note that poor people in the rural area are mobilizing themselves and start community development projects in cooperation with the government. The Department of Health and Social Development is providing government officers who visit these community development projects with the aim of helping the communities to ensure that these projects are sustainable. The labourers who are attached to the community development projects are then able to look after their families with the money they get from the projects. The communities of Mutale decided to tackle poverty through the establishment of the following community development projects: Tshandama Community Bakery, Thengwe Egg- laying, Mveledziso Catering and Decoration, Matomboni Crusher Stone and Bale Vegetable Garden. The final results from the study show that most of the rural community development projects lack proper management. The main reasons leading to poor performance of community development projects, among others are lack of financial plan, improper management style and lack of active participation of key stakeholders. The study highlighted significant information about the impact of management on the sustainability of the community development projects in Mutale Local Municipality. It was hoped that the recommendation made in this study would assist the community development projects in our country South Africa. Youth should be involved in community development projects. Community projects should be monitored regularly in order to improve the productivity. All the people who are attached to the community development projects should be trained and capacitated toward financial planning, marketing and security management.
Thesis (M.Dev) --University of Limpopo, 2010
Keywords: Sustainability; Community Development Projects; 338.90968; Economic development; Sustainable development